2021
DOI: 10.1038/s42003-021-02896-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of glycemic variability in diabetic neuropathy: a comprehensive review

Abstract: Diabetic neuropathy is one of the most prevalent chronic complications of diabetes, and up to half of diabetic patients will develop diabetic neuropathy during their disease course. Notably, emerging evidence suggests that glycemic variability is associated with the pathogenesis of diabetic complications and has emerged as a possible independent risk factor for diabetic neuropathy. In this review, we describe the commonly used metrics for evaluating glycemic variability in clinical practice and summarize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 126 publications
(128 reference statements)
0
25
0
2
Order By: Relevance
“…There are many subgroups of neuropathies, but the most common form is symmetrical diabetic peripheral neuropathy (DPN), which mainly affects the lower extremities [8], [10], [11]. DM patients with DPN often complain of symptoms such as numbness, tingling, pain, weakness, and instability when walking [6], [8], [9], [10], [12]. Our study found that foot massage therapy is effective in the healing of DPN in DM patients.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…There are many subgroups of neuropathies, but the most common form is symmetrical diabetic peripheral neuropathy (DPN), which mainly affects the lower extremities [8], [10], [11]. DM patients with DPN often complain of symptoms such as numbness, tingling, pain, weakness, and instability when walking [6], [8], [9], [10], [12]. Our study found that foot massage therapy is effective in the healing of DPN in DM patients.…”
Section: Discussionmentioning
confidence: 84%
“…DN is among the most common of all the longterm complications of DM with significant mortality and morbidity [8], [13], [5], [19], [20]. It is predicted that up to 50% of DM patients affect DN [6], [11], [21]. There are many subgroups of neuropathies, but the most common form is symmetrical diabetic peripheral neuropathy (DPN), which mainly affects the lower extremities [8], [10], [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations